1990
DOI: 10.1002/jbt.2570050404
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin degradation lipid peroxidation, and inhibition of na+/k+‐atpase in rat erythrocytes exposed to acrylonitrile

Abstract: The effect of acrylonitrile (VCN) on erythrocyte lipid metabolism was investigated in vitro in metabolically active red cells from male Sprague-Dawley rats containing three types of hemoglobins: oxyhemoglobin, methemoglobin, and carbon monoxyhemoglobin. VCN at the concentration of 10 mM rapidly depleted erythrocyte glutathione (GSH) (75% of control) and induced lipid peroxidation (274% of control). Degradation of oxy- and methemoglobin was directly proportional to the extent of lipid peroxidation (r = 0.89). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The detected MDA levels in the erythrocytes of the MM workers are in agreement with the previous reported data that showed an induction of lipid peroxidation in rats exposed to AN [15,16].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The detected MDA levels in the erythrocytes of the MM workers are in agreement with the previous reported data that showed an induction of lipid peroxidation in rats exposed to AN [15,16].…”
Section: Discussionsupporting
confidence: 95%
“…Several studies consider that it could be used as a biomarker for environmental or occupational exposure to xenobiotics capable of enzyme induction [ 13,141. AN was shown to induce lipid peroxidation in rats [15,16]. Malonaldehyde is a volatile p-scission product formed from the peroxidation of certain polyunsaturated fatty acids and is considered an index of lipid peroxidation 1171.…”
mentioning
confidence: 99%
“…Maridonneau et al (1983) reported that the generation of oxygen free radicals within human red cells induces lipid peroxidation in membranes. Farooqui et al (1990) suggested that the oxidative damage in the red cells inhibits the Na + ,K + -ATPase activity, leading to change in physical state of membrane structure. Alternatively, there may be a greater inhibition of observed Na + ,K + -ATPase activity because Na + ,K + -ATPase pump activity requires endogenous ATP.…”
Section: Discussionmentioning
confidence: 98%